INTEGRATION OF MODELING TECHNIQUES BASED ON THE LOCAL WISDOM OF TUDANG SIPULUNG IN GROUP COUNSELING TO IMPROVE STUDENT DISCIPLINE - Rahmania; Azam Arifyadi; Dhevy Puswiartika; Dian Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to determine the effectiveness of integrating modeling techniques based on the local wisdom of Tudang Sipulung in group counseling to improve students’ discipline at SMK Negeri 5 Palu. The research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The participants consisted of 60 eleventh-grade students selected through purposive sampling and divided into an experimental group and a control group. Data were collected using a student discipline questionnaire that had been validated through expert judgment and empirical testing. The experimental group received group counseling services integrating modeling techniques with the cultural values of Tudang Sipulung, while the control group received conventional counseling services. The findings showed a significant increase in students’ discipline in the experimental group, with the mean score improving from 58.43 in the pre-test to 69.33 in the post-test, while the control group showed no significant improvement. Statistical analysis using the Paired Sample T-Test produced a significance value of 0.000 < 0.05, indicating that the intervention had a significant effect on improving student discipline. The N-Gain score of 76.5% also indicated that the intervention was effective. The study concludes that integrating local cultural values into behavioral counseling techniques can strengthen students’ self-awareness, social responsibility, and disciplinary behavior in school settings.